Dynamic EMT: a multi‐tool for tumor progression - Brabletz, Simone; Schuhwerk, Harald; Brabletz, Thomas; Stemmler, Marc P. (The EMBO journal, 2021)
The process of epithelial–mesenchymal transition (EMT) is fundamental for embryonic morphogenesis. Cells undergoing it lose epithelial characteristics and integrity, acquire mesenchymal features, and become motile. In cancer, this program is hijacked to confer essential changes in morphology and motility that fuel invasion. In addition, EMT is increasingly understood to orchestrate a large variety of complementary cancer features, such as tumor cell stemness, tumorigenicity, resistance to therapy and adaptation to changes in the microenvironment. In this review, we summarize recent findings related to these various classical and non‐classical functions, and introduce EMT as a true tumorigenic multi‐tool, involved in many aspects of cancer. We suggest that therapeutic targeting of the EMT process will—if acknowledging these complexities—be a possibility to concurrently interfere with tumor progression on many levels. Graphical Abstract This review contrasts classical and non‐classical roles of epithelial‐mesenchymal transition in diverse aspects of cancer cell biology.